2014
DOI: 10.1007/s10552-014-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal reproductive history, fertility treatments and folic acid supplementation in the risk of childhood acute leukemia: the ESTELLE Study

Abstract: The findings do not suggest that infertility and fertility treatments are risk factors for CL. They suggest that maternal histories of stillbirth and miscarriage may be more frequent among mothers of CL cases and that folic acid supplementation during preconception may reduce the risk of CL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
3
33
0
2
Order By: Relevance
“…The results of recent reports are in line with our findings, such as the ESTELLE case–control study, a French investigation of smaller size compared with the NARECHEM‐BT study, which also reported statistically significant specific associations between maternal history of stillbirth and miscarriage and ALL (OR: 2.6, 95% CI 1.1–5.9) and AML (OR: 1.8, 95% CI 1.1–2.8). In contrast, another French study (Etude Sur les Cancers et les Leucémies de l'Enfant (ESCALE), Study on Environmental and Genetic Risk Factors of Childhood Cancers and Leukemia) reported a null association between history of miscarriages and ALL or AML.…”
Section: Commentsupporting
confidence: 91%
“…The results of recent reports are in line with our findings, such as the ESTELLE case–control study, a French investigation of smaller size compared with the NARECHEM‐BT study, which also reported statistically significant specific associations between maternal history of stillbirth and miscarriage and ALL (OR: 2.6, 95% CI 1.1–5.9) and AML (OR: 1.8, 95% CI 1.1–2.8). In contrast, another French study (Etude Sur les Cancers et les Leucémies de l'Enfant (ESCALE), Study on Environmental and Genetic Risk Factors of Childhood Cancers and Leukemia) reported a null association between history of miscarriages and ALL or AML.…”
Section: Commentsupporting
confidence: 91%
“…It is also hypothesized that the association with childhood cancers may be due to factors related to underlying subfertility rather than the treatment for infertility itself, as assessed in several studies. Most studies that investigated time to pregnancy or the need for medical consultation for infertility found no association with leukemia, but these studies did not differentiate between women who received treatment for infertility or not [4954]. A study in Denmark obtained information from the Danish Infertility Cohort, which consists of women with fertility problems referred to medical facilities in Denmark and those with a diagnosis of infertility from the National Patient Register or the Danish IVF registry (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A study in France showed an association between leukemia and ovulation induction but not with in vitro fertilization [42]. Another study by the same group in France did not confirm this association nor with specific types of ovulation induction medication [43]. Finally, it is possible that the association with ovulation induction treatment might be related to factors underlying fertility problems [44], and not the treatment itself.…”
Section: Discussionmentioning
confidence: 99%